Historical Path Dependence in the Turkish Automobile Industry and the Possibility of Path Creativity - Dolanay, Sitki Selim (Recent Trends in Arts and Social Studies Vol. 6, 2023)
The geographical continent transition taking place among Turkey’s automotive industry, within the limits of qualitative studies, creating a historical perspective, the region, released today stems from the importance of global integration centers. In this context, Turkey is located between geographic continent transitions to create operating limits of the automotive industry, the global integration of the indicator is due primarily to the fact that the reveal. Thus, while Turkey is an attractive market for car production, on the other hand, sufficient improvement over time in the production of trucks and other automotive products, such as buses has not been achieved. Regarding Turkey, the 1929 experience appears to have been successful. As a result, OYAK and TOFA had to wait until 1971 to set up an automotive assembly facility with licence agreements. There has been a noticeable increase in sectoral production numbers since the opening of two automotive facilities, but this trend has not been adequately supported by the government through the incentive system, and in the late 1970s the production of the automotive industry has decreased. At the beginning of the last century, the vehicle industry, which was shaped under the structural developments on the functional efficiency of the horse carriage, gave birth to the mass and mass production techniques formed by Ford with the concept of competition. It can produce prototypes in a short period of four months in Turkey in 1961, as evidenced by an indication of the dependency on a long time wasting which is not technology importation pathway, such as five years. How to break the path of devotion demonstrates that it is a difficult job. Path dependency is thought to result from the education system.